2016
DOI: 10.1016/j.neures.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

PSD-95 regulates synaptic kainate receptors at mouse hippocampal mossy fiber-CA3 synapses

Abstract: Kainate-type glutamate receptors (KARs) are the third class of ionotropic glutamate receptors whose activation leads to the unique roles in regulating synaptic transmission and circuit functions. In contrast to AMPA receptors (AMPARs), little is known about the mechanism of synaptic localization of KARs. PSD-95, a major scaffold protein of the postsynaptic density, is a candidate molecule that regulates the synaptic KARs. Although PSD-95 was shown to bind directly to KARs subunits, it has not been tested wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Several synapse-associated proteins, especially PSD95 protein, were identified as interacting proteins for the kainate receptors [ 45 , 46 , 47 ]. For example, co-immunoprecipitations using rat brain extracts showed that GRIK2 and GRIK5 proteins were associated with the PSD95 protein [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several synapse-associated proteins, especially PSD95 protein, were identified as interacting proteins for the kainate receptors [ 45 , 46 , 47 ]. For example, co-immunoprecipitations using rat brain extracts showed that GRIK2 and GRIK5 proteins were associated with the PSD95 protein [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…What constitutes a KAR synaptic slot remains an open question. Possibilities include PDZ-domain-containing proteins such as PSD95, PICK or GRIP 14 15 37 54 , although re-expression of a mutated GluK2a subunit lacking the four last amino acids responsible for the interaction with PDZ domain proteins did not affect KAR-EPSCs. In contrast, removal of the last 14 amino acids of GluK2a strongly had an impact on the amplitude of KAR-EPSCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, PSD-95 not only mediates aforesaid complexes, but also fulfils crucial roles in maintaining and regulating the three-dimensional molecular structures at the postsynaptic density of glutamatergic synapses (Chen et al, 2011). In particular, PSD-95 knockout mice were associated with reduced hippocampal KAR contents (Suzuki and Kamiya, 2016), indicating that IR drug-mediated reductions of PSD-95 may also be neuroprotective against KA toxicity through subsequent decreases of synaptic KAR contents.…”
Section: Discussionmentioning
confidence: 99%